Influence of renal and hepatic impairment on the pharmacokinetics of anacetrapib. (6th June 2014) - Lauring, Brett; Li, Xiujiang (Susie); Liu, Yang; Corr, Christy; Lazarus, Nicole; Cote, Josee; Larson, Patrick; Levonas, Amy O. Johnson; Lasseter, Kenneth C.; Preston, Richard A.; Smith, William B.; Lai, Eseng; et al.
Abstract Two open‐label, parallel‐group studies evaluated the influence of renal and hepatic insufficiency on the pharmacokinetics of a single‐dose anacetrapib 100 mg. Eligible participants included adult men and women with moderate hepatic impairment (assessed by Child–Pugh criteria) or severe renal impairment (CrCl <30 mL/min/1.73 m2). In both studies, patients were matched (race, age, sex, BMI) with healthy control subjects. Twenty‐four subjects were randomized in each study (12 with either moderate hepatic or severe renal impairment and 12 matched healthy controls). In the hepatic insufficiency study, the geometric mean ratio (GMR; mean value for the group with moderate hepatic insufficiency/mean value for the healthy controls) and 90% CIs for the area under the concentration–time curve from time zero to infinity (AUC0–∞) and the maximum concentration of drug in plasma (Cmax) were 1.16 (0.84, 1.60) and 1.02 (0.71, 1.49), respectively. In the renal insufficiency study, the GMRs (mean value for the group with severe renal insufficiency/mean value for the healthy controls) and 90% CIs for AUC0–∞ and Cmax were 1.14 (0.80, 1.63) and 1.31 (0.93, 1.83), respectively. Anacetrapib was generally well tolerated and there was no clinically meaningful effect of moderate hepatic or severe renal insufficiency on the pharmacokinetics of anacetrapib.